2021
DOI: 10.1155/2021/6683014
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Level Assessment of Smoking Cessation following a Diagnosis of Tobacco- or Nontobacco-Related Cancer among United States Adults

Abstract: Introduction. Smoking cessation after a cancer diagnosis can significantly improve treatment outcomes and reduce the risk of cancer recurrence and all-cause mortality. Aim. We sought to measure the association between cancer diagnosis and subsequent smoking cessation. Methods. Data was sourced from the Population Assessment of Health and Tobacco (PATH) study, a representative population-based sample of United States adults. Our analytic sample included all adult smokers at Wave I, our baseline. The exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…6 Secondary prevention strategies and measures (eg, exercise intervention and smoking cessation) affecting behaviour changes after NCD diagnosis have been shown to be effective and should be emphasised particularly for middle-aged and older adults because they are at higher risk of NCD diagnosis. 7,8 Previous cross-sectional studies have suggested that behavioural risk factors of NCDs were strongly associated with socioeconomic status (SES); 9 however, less is known about the direction and the extent to which SES might influence longitudinal behaviour changes before and after the diagnosis of NCDs. Examining how individuals respond to NCD diagnoses and any differences therein by SES is crucial to better understand the value of NCD screening programmes, to assess the adequacy of secondary prevention interventions, and to understand disparities in NCD management.…”
Section: Introductionmentioning
confidence: 99%
“…6 Secondary prevention strategies and measures (eg, exercise intervention and smoking cessation) affecting behaviour changes after NCD diagnosis have been shown to be effective and should be emphasised particularly for middle-aged and older adults because they are at higher risk of NCD diagnosis. 7,8 Previous cross-sectional studies have suggested that behavioural risk factors of NCDs were strongly associated with socioeconomic status (SES); 9 however, less is known about the direction and the extent to which SES might influence longitudinal behaviour changes before and after the diagnosis of NCDs. Examining how individuals respond to NCD diagnoses and any differences therein by SES is crucial to better understand the value of NCD screening programmes, to assess the adequacy of secondary prevention interventions, and to understand disparities in NCD management.…”
Section: Introductionmentioning
confidence: 99%
“…Our observed rate of 61.7% of current smoking may therefore not be a generalizable prevalence rate of continued smoking. Nevertheless, the percentage of current smokers is not unusual, and other studies have indicated that a substantial proportion of smokers continue to smoke after a diagnosis [ 18 , 63 , 64 ]. Older studies on cessation rates in Jordanian cancer patients also indicate that relapse rates are very high [ 16 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 However, urologists are not universally screening for tobacco use, and few are using evidence-based treatment strategies for their patients. 1,[16][17][18] Previously hypothesized barriers to urologists' use of these EBPs include competing clinical priorities, time constraints, and a lack of comfort with providing counseling and prescribing medications. 16 In other specialties, frameworks such as the 5 A's have successfully facilitated the use of EBPs for tobacco screening and treatment.…”
Section: Introductionmentioning
confidence: 99%